A Study of Trauma Patients in the Emergency Department of a Tertiary Care Hospital in Nepal during Lockdown in COVID-19 Pandemic - Shrestha, S. K.; Dahal, S.; Bhattarai, A. (Kathmandu University Medical Journal, 2022)
Background The nationwide lockdown was imposed upon by the Government of Nepal with regards to the COVID-19 pandemic. Even during times of limited mobility and travel, trauma cases were presenting to the hospital. Objective To assess trauma patterns among patients presented to the Emergency department in Dhulikhel hospital during the lockdown period. The assessment of the burden of trauma during the pandemic could aid in planning allocation of resources and improving trauma care. Method A retrospective cross-sectional study design was used to assess all patients with a history of trauma during the period of lockdown announced by the Government of Nepal for COVID-19 from March 24 to June 14, 2020. Result Among 2097 patients that visited the emergency department, 23% were trauma cases. In comparison to the corresponding time-period in 2019, trauma cases reduced by more than half (54.5%). The majority of patients utilized ambulances as a means of transportation; a few patients utilized Dhulikhel emergency medical services. The most common mechanism of injury was fall injury, followed by motor vehicle accident and physical assault. Traumatic brain injury occurred in 30% of patients. Of all patients, 71% were discharged after initial treatment, 26% were admitted to different wards and 3% were referred to other health centres. Conclusion Fall injury is a crucial public health concern followed by motor vehicle accident among trauma patients even during the pandemic condition. Thus, emergency rooms should aid in planning for preparedness, mitigation of trauma during situations like these, in planning the allocation of resources and improving trauma care.